Insights into Mechanochemical Reactions at Targetable and Stable, Sub‐ambient Temperatures. Issue 40 (5th September 2018) - Andersen, Joel; Mack, James
Abstract: We provide insights into the effects of stable and verifiable, low‐temperature conditions on mechanochemical reactions. These are made possible by modifications made to a SPEX 8000 m Mixer/mill allowing reliable fine control of low‐temperature mechanochemical reactions. Using the reduction of 4‐tert‐butylcyclohexanone as a model system we find the diastereomeric product distribution bore a strong dependence on the selected temperature. The same reduction in methanol at room temperature shows similar stereoselectivity trends. In both cases decreasing temperature favors increases in selectivity, although the effect is more pronounced in the solvent‐free mechanochemical conditions. These results indicate that the cooled jar provides a heatsink to mitigate the exothermic character of the reaction. Stereoselectivity also showed a dependence on operating frequency, although the nature of this dependence remains unclear. Applications of our reactor extend far beyond what is presented herein. Abstract : Ground out : The effects of low‐temperature conditions on mechanochemical reactions are studied using the reduction of 4‐ tert ‐butylcyclohexanone as a model system. Comparison is made with methanol at room temperature. When either temperature or frequency is varied, both cases demonstrate significant changes to stereoselectivity. The unique reactor employed has potential for use in many other applications